The presence of heparin binding proteins and their impact on semen quality of Holstein Friesian bulls - KRISHNAN, G; THANGVEL, A; LOGANATHASAMY, K; VEERAPANDIAN, C; KUMARASAMY, P; KARUNAKARAN, M (The Indian Journal of Animal Sciences, 2016)
Present study was designed to evaluate the semen quality of breeding bulls positive for 24 and 30 kDa heparin binding proteins (HBPs) in the semen. Seventeen Holstein Friesian breeding bulls were screened for 24 and 30 kDa HBPs in semen by heparin-sepharose affinity chromatography and SDS-PAGE, and grouped into three based on presence/absence of HBPs. In vitro characteristics of spermatozoa were assessed by standard analysis of sperm abnormalities, functional membrane integrity, acrosome integrity and sperm chromatin integrity in fresh and frozen- thawed semen. Bulls positive for 30 kDa had lowest sperm abnormalities and sperm chromatin fragmentation than bulls positive for 24 kDa and without HBPs in the fresh ejaculates. Further, fresh semen positive for 30 kDa had 8.76% of higher active plasma membrane with 7.63% intact acrosome. The process of cryopreservation of semen increased sperm abnormalities, acrosome damage and chromatin fragmentation in all the semen samples irrespective of presence/absence of HBPs. However, semen samples positive for 24 and 30 kDa HBPs were able to sustain lower percentage of post-thaw sperm abnormalities with higher chromatin integrity in comparison to semen devoid of HBPs. Moreover, semen with 24 and 30 kDa HBPs had higher post-thaw intact acrosome with active plasma membrane than negative semen. The results concluded that bulls positive for 30 kDa had 12.43 and 28.37 percentages of better semen quality than bulls with 24 kDa and devoid of HBPs.